Manajemen Sekolah Berbasis Pendidikan Lingkungan dalam ‎Pembentukan Karakter Peduli Lingkungan Siswa: Kajian ‎Literatur Integratif - Samsul Hadi (WISE Pendidikan Indonesia, 2026)
Environmental education has become an essential agenda in school management because ecological awareness must be translated into students’ values, habits, and responsible behavior. This study aims to synthesize previous research on the integration of environmental education into school management to strengthen students’ environmental care character. This study employed an integrative literature review by analyzing relevant studies published between 2018 and 2025 on school management, environmental education, green schools, Adiwiyata programs, school culture, environmental literacy, and pro-environmental behavior. The reviewed literature was analyzed thematically to identify recurring patterns related to institutional policy, curriculum integration, school culture, stakeholder participation, environmental facilities, and program evaluation. The findings indicate that environmental education is more effective when it is embedded in school management through strategic planning, curriculum implementation, daily habituation, teacher and principal role modelling, student participation, supportive infrastructure, and continuous evaluation. The synthesis also shows that students’ environmental care character is not formed merely through classroom instruction, but through a consistent school ecosystem that integrates cognitive, affective, behavioral, cultural, and managerial dimensions. This study contributes a conceptual framework of environmental education-based school management, in which institutional, pedagogical, cultural, participatory, ecological-practical, and evaluative components work together to shape students’ environmental responsibility. The implication of this study is that schools should position environmental education as an integral part of institutional governance rather than as an additional, ceremonial, or award-oriented program.